José Celestino Mutis' appropriation of Newton's experimental physics in New Granada (1761–1808). (September 2019) - Orozco-Echeverri, Sergio H.; Molina-Betancur, Sebastián
This paper characterizes José Celestino Mutis' (1732–1808) appropriation of Newton in the Viceroyalty of New Granada. First, we examine critically traditional accounts of Mutis' works highlighting, on the one hand, their inadequacy for directing their claims toward the nineteenth-century independence from Spain and, on the other, for not differentiating between Newtonianism and Enlightenment. Next, we portray Mutis' complex Newtonianism from his own statements and from printed sources, including a variety of works and translations from British, Dutch, and French authors, in addition to a wide range of Newton's writings, unusual for an eighteenth-century reader in the Americas. Finally, we analyze a salient claim of Mutis' Newtonianism in order to depict his appropriation and transformation of Newton's ideas: the characterization of Newtonian experimental physics as a useful science. In so doing, Mutis further developed metaphysical and methodological positions not present in Newton's works.